Interference with the germination and growth of Ulva zoospores by quorum‐sensing molecules from Ulva‐associated epiphytic bacteria. (23rd July 2013) - Twigg, Matthew S.; Tait, Karen; Williams, Paul; Atkinson, Steve; Cámara, Miguel
Summary Ulva zoospores preferentially settle on N‐acylhomoserine lactone (AHL) producing marine bacterial biofilms. To investigate whether AHL signal molecules also affect the success and rate of zoospore germination in addition to zoospore attraction, the epiphytic bacteria associated with mature Ulva linza were characterized and bacterial isolates representative of this community tested for the ability to produce AHLs. Two of these AHL‐producing isolates, Sulfitobacter spp. 376 and Shewanella spp. 79, were transformed with plasmids expressing the Bacillus spp. AHL lactonase gene aiiA to generate AHL‐deficient variants. The germination and growth of U. linza zoospores was studied in the presence of these AHL‐deficient strains and their AHL‐producing counterparts. This revealed that the AHLs produced by Sulfitobacter spp. and Shewanella spp. or the bacterial products they regulate have a negative impact on both zoospore germination and the early growth of the Ulva germling. Further experiments with Escherichia coli biofilms expressing recombinant AHL synthases and synthetic AHLs provide data to demonstrate that zoospores germinated and grown in the absence of AHLs were significantly longer than those germinated in the presence of AHLs. These results reveal an additional role for AHLs per se in the interactive relationships between marine bacteria and Ulva zoospores.